The Innovation of Interpretation for Tourism through Eco-Museum - Sanyakoon, Prapaporn; Nonsiri, Petchsri (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2023)
The tourism interpretation plays an important role of success in tourism management of Thai tourism community. However, lacking of knowledge and know-how of tourism interpretation drives to study on 1) the innovation of interpretation for tourism through eco-museum 2) the tourist experiences perceived from the innovative interpretation for tourism through eco-museum in Thailand. The research employed the qualitative method. The data were collected by in-depth interview with eight representatives of government organizations and the eco-museum stakeholders, 19 local curators or local people and 18 tourists who visit three eco-museums in Trat Province such as Eco-museum of Yaimom Eco-museum of Taranae, and Eco-museum of Changtune. The data were also collected by the participatory observation on tourism activities in the three eco-museums. The findings were shown the innovative tourism interpretation through local curators, tourism activities, offline and online media. The innovative interpretation created the tourist experiences such as understanding, appreciation and consciousness towards community. The results can be applied in developing local tourism interpretation or other forms of tourism. The effective interpretation certainly leads to tourism pleasure and experiences with quality.